Smart antenna design alimented by a 4x4 butler matrix - S. Almorabeti; H. Terchoune; M. Rifi; H. Tizyi; S. Smihily (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
In the last decades, the development of efficient antennas for wireless power transfer applications has gained great attention from researchers worldwide and has become a vital research topic. In this paper, we propose the optimum design and implementation in microstrip technology of a switched beam smart antenna alimented by a 4x4 butler matrix (BM) for a microwave wireless power transmission system (MPT) at 5.8 GHz. The proposed smart antenna consists of a four linear microstrip patch antenna array and a 4x4 butler matrix beamforming network. It was able to form and steer four orthogonal beams in the four directions (±39°, and ±15°). Furthermore, it exhibited a high gain of 17.98 dB and good simulated and measured return losses. The design, optimization and simulation of the smart antenna components were performed using advanced design system (ADS).